Effects of Different Harvest Times on Nutritional Component of Herbaceous Peony Flower Petals - Weixing Li; Xiaomei Song; Yanmin Hua; Jun Tao; Chunhua Zhou (Journal of Chemistry)
Herbaceous peony (Paeonia lactiflora Pall.) flowers can be used as edible flowers, but few studies concerned about their edible values and the optimal harvest season. In this study, petals of three herbaceous peony cultivars including “Dafugui,” “Hongyan Zhenghui,” and “Yangfei Chuyu” at four different development stages were used as materials to measure the content of soluble sugar, organic acid, protein, vitamin C (Vc), total phenolics, total flavonoids, mineral elements, and superoxide dismutase (SOD) activity, with the aim to understand the variation tendency of the nutritional ingredients and bioactive components in herbaceous peony flower petals during development and to determine the optimal harvest time for herbaceous peony flowers with better edible qualities. The results demonstrated that the content of individual nutritional and bioactive components was varied with cultivars and developmental stages. The soluble sugar content was 63.69–225.97 mg/g FW, organic acid 10.13–24.60 mg/g FW, soluble protein 9.83–39.17 mg/g FW, Vc 12.31–33.52 mg/100 g FW, total phenolics 83.23–136.19 mg/g DW, total flavonoids 10.20–24.98 mg/g DW, and SOD activity 62.92–284.09 U/g FW. For mineral elements, the content of Na, Mg, K, Ca, Mn, Fe, Ni, and Zn was 20.96–65.51 μg/g DW, 810.85–1342.36 μg/g DW, 6723.68–12253.63 μg/g DW, 848.67–3038.46 μg/g DW, 1.14–8.44 μg/g DW, 48.70–149.72 μg/g DW, 1.20–2.17 μg/g DW, and 16.69–25.50 μg/g DW, respectively. The content of soluble sugar, protein, total flavonoids, and SOD activity in flower petals was the highest, and the content of organic acid was the lowest at the full bloom period (S3) for all three cultivars, while the highest Vc and total phenolics were at the early bloom stage (S2) and flower bud stage (S1), respectively. In conclusion, it is recommended to harvest herbaceous peony flowers at S3 with the best edible quality considering nutrients and bioactive components.